Characterisation of urban runoff pollution in Paris - Gromaire-Mertz, M.C.; Garnaud, S.; Gonzalez, A.; Chebbo, G. (Water Science and Technology, 1999)
Runoff was collected from 4 roofs, 3 courtyards and 6 streets on an experimental catchment in central Paris, and analysed for SS, VSS, GOD, BOD5, hydrocarbons, heavy metals both as regards dissolved and particle fractions. Whereas street runoff showed important SS, COD and hydrocarbon loads, roof runoff was noticeable for its high concentration of heavy metals. These concentrations in comparison with water quality standards enhance the importance of runoff pollution. The use of sample settling for runoff treatment is discussed on the basis of data concerning the distribution between dissolved and particle bound pollution loads, along with settling velocity measurements. Runoff particles were found to be highly contaminated with heavy metals and hydrocarbons, which raised the problem of sludge disposal. (C) 1999 IAWQ Published by Elsevier Science Ltd. All rights reserved.